Microbial enzymatic activities in soils of Vojvodina, Serbia: insights into the relationship with chemical soil properties - Kuzmanović, Ana; Tamindžija, Dragana; Ninkov, Jordana; Vasin, Jovica; Đurić, Simonida; Milić, Stanko; Radnović, Dragan (Archives of Biological Sciences, 2024)
Paper description: As a significant source of biodiversity, soil is under immense pressure due to indiscriminate exploitation. Microorganisms, a dominant biogenic component of the pedosphere, promptly respond to changes in the soil, which makes them excellent indicators of its quality. Appropriate microbial enzyme synthesis is usually the first response of the microbial community to changes in the environment. The relationship between microbial enzymes and the chemical properties of dominant soil types in Vojvodina, Serbia were examined. Results reveal correlations between specific enzymes and soil chemical properties. Findings point to the possibility of the application of enzymatic activities in agricultural soil quality monitoring. Abstract: For an agricultural region such as the Vojvodina Province in northern Serbia, soil quality monitoring is very important. Enzymatic activities are proposed as good indicators as they respond to even the slightest changes in the soil. This study aimed to analyze the enzymatic activity levels across three different soil types in Vojvodina and to examine their connection to soil chemical properties and land use. All soil types (chernozem, vertisol, solonchak) were sampled at nine locations, each with 3 field plots. The activities of acid and alkaline phosphatase, β-glucosidase, dehydrogenase, and catalase were measured in samples, as well as the selected chemical properties. Results showed differences in enzymatic activity across different soil types and land use. The most active enzymes in vertisol were acid phosphatase and β-glucosidase; in solonchak, it was alkaline phosphatase; in chernozem, it was dehydrogenase. A high correlation between enzymatic activities and certain soil chemical properties (pH reaction, organic matter, organic carbon, total nitrogen) was also observed, underlining the existence of a relationship between different soil components. The highest determined correlation was between acid phosphatase and pH (r=-0.7), alkaline phosphatase and total nitrogen (r=0.7), and organic matter (r=0.72); the obtained correlations were found to be statistically significant.